Confirmation of the Structure of Trans‐Cyclic Azobenzene by X‐Ray Crystallography and Spectroscopic Characterization of Cyclic Azobenzene Analogs. Issue 9 (6th March 2018) - Jun, Meesook; Joshi, Dhruval K.; Yalagala, Ravi S.; Vanloon, Jesse; Simionescu, Razvan; Lough, Alan J.; Gordon, Heather L.; Yan, Hongbin
Abstract: The photoisomerization properties of a series of cyclic azobenzene (cAb) analogs, including non‐substituted, Br‐, CN‐, carboxyl‐, and amino cAb, were compared. While the trans ‐form of these analogs show different degrees of thermal stability, no spectral changes in the absorption wavelengths were observed for amino cAb upon exposure to purple light. The 15 N NMR chemical shifts of cAb in both cis ‐ and trans ‐forms were found to show a large difference from those of aromatic azobenzene; however, the trend of difference in chemical shift is in agreement with that obtained from quantum chemical calculations. More importantly, the structure of the photoisomerization product from cis ‐cAb was confirmed to be, indeed, the trans ‐cAb by X‐ray diffraction experiments. The 15 NMR data of the cAb isomers and confirmation of trans ‐cAb through crystal structure will be of importance for future studies in the design and applications of cAb as a photoswitch. Abstract : The structure of trans ‐cyclic azobenzene was confirmed by X‐ray crystallography. The 15 N NMR chemical shifts of cis ‐ and trans ‐cyclic azobenzene were computed and determined experimentally. The photoisomerization properties of the unmodified, bromo‐, cyano‐, carboxyl‐ and amino‐cyclic azobenzene were compared.